Gravity estimation of the intensive and extensive margins of trade: An alternative procedure with alternative data - Harry Flam; Håkan Nordström (Center for Economic Studies and ifo Institute (CESifo), 2011)
Helpman, Melitz and Rubinstein (2008) derive gravity equations to estimate effects of trade barriers on the intensive and extensive margins of trade. They exploit the frequency of zeros in aggregate bilateral trade data to identify effects on the extensive margin and to obtain controls for firm level heterogeneity and sample selection on the intensive margin. By using data on the number of bilaterally traded products we improve on identification and allow estimation of the extensive margin when data contain only positive trade flows. We also control for the pervasive presence of heteroscedasticity in trade data. The heterogeneity and selection biases are shown to be small and unimportant whereas the heteroscedasticity bias is large and important.
Keywords: F10; F12; F14; 330; gravity estimation; heteroscedasticity in data; intensive and extensive margin; Außenwirtschaft; Gravitationsmodell; Handelsspanne; Schätzung; Heteroskedastizität; Welt